Pengendalian Pekerjaan Proyek Konstruksi Studi Kasus Pembuatan Pintu Air di Desa Bakung Kecamatan Batumandi Kabupaten Balangan - Angraini, Lini (Lambung Mangkurat University Press, 2024)
The Bakung Village watergate construction began in early September and concluded on October 9, 2023. If the physical construction of the water gate deviates significantly from the planned schedule, there is a concern that the project will be disrupted by high water flow in the fields. This situation could lead to the failure of the Bakung Village water gate project due to the high water volume in the fields. Additionally, supervision of the specifications and volume of each work unit is necessary to ensure that the constructed structure can be used properly and safely. Time and quality control are essential to ensure the project is completed successfully according to the contract. The method used for time control is the bar chart/graph. For quality control, the method involves comparing the actual work's specifications and volume of unit prices with the planning stated in the contract. Supervision and control are carried out by verifying the contractor's project results using documents and direct monitoring in the field. The total duration of the work is 40 calendar days. The contractor could carry out the work according to the technical specifications, and the volume of each work unit stated in the contract. Based on daily and weekly reports from the supervising consultant and field inspections, the Bakung Village water gate construction was completed according to the contract agreement.